La aplicación metodológica del bloque curricular N°3 movimiento formativo, artístico y expresivo para la educación rítmica de los niños de séptimo año de la unidad educativa Lauro Damerval Ayora N°1 de la ciudad de Loja - Yaguana Macas, José Wilfrido (2015)
This research work is aimed to meet the Methodological Curriculum Implementation of Block No. 3 artistic and expressive rhythmic education for children seventh year of the educational unit N1 Lauro Damerval Ayora city of Loja educational movement. This block expects the student to the harmonious care of your body, body language, sports, marked in its formative, artistic and expressive movement object, by the third curricular currently Proper methodology is very important as it will help the comprehensive correct formation of the child and the development of their skills. The research is qualitative. The type of study was longitudinal and pre-experimental design. The objective is aimed to analyze, define the methodology used by teachers in teaching curricular, for rhythmic education and improve training and rhythmic coordination of students. specific objectives: theoretically justify the appropriate methodology for teaching third-curricular learning and rhythmic education students, diagnose the current state of the methodology used by teachers for teaching third and rhythmic curricular education students in the educational unit Lauro Damerval Ayora, propose, implement and validate a program of methodological exercises for teaching third curricular learning and improving rhythmic education of students in research for the purposes of this thesis have used some research methods such as the induction, deduction, -synthesis analysis, historical logical, empirical observation and survey methods, theoretical modeling methods, systems approach, probabilistic, mathematician, content analysis, cyber, empirical evidence scientific methods is based on fieldwork with support of different instruments including survey allowed us to collect data. It was found that seventh graders are performing poorly in the third curricular learning about the lack of methodology for teachers of Physical Culture. Getting the author to the conclusion that there is failure in the formation and rhythmic coordination of students by the lack of planning and implementation of basic gymnastic exercises, rounds, movements and body language by teachers of physical culture of the educational unit Lauro Damerval Ayora No.1.